Letterwork / Creative Letterforms in Graphic Design - Neuenschwander Brody (Phaidon Press Limited, 1993)
Introduction, Conveying the Message, Lettering as Image, Lettering and Typography, The Design of Letters, New Directions, Directory, Further Reading, Index.
Introduction, Conveying the Message, Lettering as Image, Lettering and Typography, The Design of Letters, New Directions, Directory, Further Reading, Index.